Execution of Quality by Design Approach in the Formulation of Fluconazole Inclusion Complex Based Suppository for Vaginal Candidiasis - Kanojiya, Pranita Sunil; Wadetwar, Rita Naresh; Godbole, Amita Prasanna (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: The present work was carried out to improve the aqueous solubility of Fluconazole by formulation of inclusion complex using β-cyclodextrin and then loaded into the suppository for the treatment of vaginal candidiasis. Material and Methods: Fluconazole (FOZ) Inclusion Complex (INC) with β-Cyclodextrin (βCD) was formulated first after optimization of the D-Optimal mixture design for the molar ratio. Then INC was prepared (1:1 molar ratio) with different methods (kneading, coprecipitation and microwave irradiation) and was studied for FTIR, DSC and XRD studies. Results: Microwave irradiation (MW) was the best method for the preparation of INC with the maximum % drug content (98.96±1.78%) and solubility (3.14±0.85 mg/mL). The QbD approach was employed to select the best ratio of the base and plasticizer for the suppository. The suppository was prepared using PEG 6000 (base) and PEG 400 (plasticizer) and an optimized inclusion complex was incorporated. The D-Optimal mixture design was applied to optimize a combination of PEG 6000 and PEG 400 by studying responses such as hardness, melting time and drug release from the suppository. The in vitro release study showed that higher drug release was achieved from the FOZ MW INC based suppository (99.40±1.43%) compared to the plain drug suppository (71.41±2.19%). Conclusion: The prepared FOZ suppository had higher drug release and enhanced antifungal activity. Therefore, it would be beneficial in the treatment of Vaginal Candidiasis.
Keywords: D-Optimal mixture design; Fluconazole; Inclusion complex; Solubility enhancement; Vaginal Candidiasis; β-cyclodextrin